Novel regulatory mechanisms for the CFTR gene - Ott, Christopher J. (2009)
The CFTR (cystic fibrosis transmembrane conductance regulator) gene, which when mutated causes cystic fibrosis, encompasses nearly 200 kb of genomic DNA at chromosome 7q31.2. It is flanked by two genes ASZ1 [ankyrin repeat, SAM (sterile α-motif) and basic leucine zipper] and CTTNBP2 (cortactin-binding protein 2), which have very different expression profiles. CFTR is expressed primarily in specialized epithelial cells, whereas ASZ1 is transcribed exclusively in the testis and ovary, and CTTNBP2 is highly expressed in the brain, kidney and pancreas, with lower levels of expression in other tissues. Despite its highly regulated pattern of expression, the promoter of the CFTR gene apparently lacks the necessary elements to achieve this. We previously suggested that cis-acting regulatory elements elsewhere in the locus, both flanking the gene and within introns, were required to co-ordinate regulated, tissue-specific expression of CFTR. We identified a number of crucial elements, including enhancer-blocking insulators flanking the locus, intronic tissue-specific enhancers and also characterized some of the interacting proteins. We recently employed a high-resolution method of mapping DHS (DNase I-hypersensitive sites) using tiled microarrays. DHS are often associated with regulatory elements and use of this technique generated cell-specific profiles of potential regulatory sequences in primary cells and cell lines. We characterized a set of cis-acting elements within the CFTR locus and demonstrated direct physical interaction between them and the CFTR promoter, by chromosome conformation capture (3C). These results provide the first insight into the three-dimensional structure of the active CFTR gene.